Appropriateness of Antibiotic Prescribing in U. S. Children's Hospitals: A National Point Prevalence Survey. (4th October 2017) - Tribble, Alison; Lee, Brian; Handy, Lori; Gerber, Jeffrey S; Hersh, Adam L; Kronman, Matthew; Terrill, Cindy; Newland, Jason; ,
Abstract: Background: Multiple studies estimate that inappropriate antibiotic prescribing ranges from 30–50% in hospitalized patients, but few have included pediatric patients. Pediatric studies characterizing inappropriate prescribing are needed to target and improve antimicrobial stewardship program (ASP) efforts. Methods: Cross-sectional analysis of antimicrobial prescribing at 30 U.S. children's hospitals. Participating hospitals were academic, tertiary care hospitals in the Sharing Antimicrobial Reports for Pediatric Stewardship (SHARPS) collaborative. Subjects were children 0–17 years with an active antibiotic order at 0800 on a single day during three consecutive calendar quarters (Q3 2016 – Q1 2017). Each hospital's ASP used a standardized survey to collect data on antibiotic orders and evaluate appropriateness. Data were pooled from the three surveys. The primary outcome was the pooled estimate for the percentage of prescriptions classified as inappropriate. Secondary outcomes were pooled estimates for indication, reason for inappropriate use, and ASP review status for each antibiotic. Results: Of 19, 598 children hospitalized on survey days, 6, 922 (35%) had ≥1 active antibiotic order. Median age of children receiving antibiotics was 3.7 years (0.5, 10.9). Figures 1 and 2 show the most common antibiotics and indications. Of all antibiotic orders, 1, 514 (15%) were classified as inappropriate, and 19% of patients with antibiotic orders had at least one inappropriate order. The most common reasons for inappropriate use were bug-drug mismatch (26%), surgical prophylaxis > 24 hours (18%) and unnecessary duplicate therapy (12%). ASPs would not have routinely reviewed 50% of all inappropriate orders. An additional 22% of inappropriate orders were for antibiotics typically reviewed by ASPs, but were yet to be reviewed at the time of the survey. Conclusion: Across 30 children's hospitals, approximately 1 in 3 hospitalized children is receiving an antibiotic at any given time. Almost 20% of these children are receiving inappropriate therapy, and a substantial portion of inappropriate use is not captured by current ASP practices. Disclosures: C. Terrill, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant; J. Newland, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant.